Aerobic Oxidation of Benzyl Alcohol in a Continuous Catalytic Membrane Reactor - Constantinou, Achilleas; Wu, Gaowei; Venezia, Baldassarre; Ellis, Peter; Kuhn, Simon; Gavriilidis, Asterios (My University, 2019)
A catalytic membrane reactor with a Au–Pd catalyst, impregnated at the inner side of the membrane, was studied in the catalytic oxidation of benzyl alcohol in flow. The reactor comprised of four concentric sections. The liquid substrate flowed in the annulus created by an inner tube and the membrane. The membrane consisted of 3 layers of α-alumina and a titania top layer with 5 nm average pore size. Oxygen was fed on the outer side of the membrane, and its use allowed the controlled contact of the liquid and the gas phase. Experiments revealed excellent stability of the impregnated membrane and selectivities to benzaldehyde were on average > 95%. Increasing the pressure of the gas phase and decreasing liquid flowrates and benzyl alcohol concentration resulted in an increased conversion, while selectivities to benzaldehyde remained constant and in excess of 95%.
Keywords: Gold/palladium catalyst; Catalytic oxidation; Continuous flow; Membrane reactor; Ceramic membrane